About the Challenges of Cybercrime in the Digital Age (UNWE Yearbook, 2022)
With the COVID-19 pandemic and The Fourth Industrial Revolution: Digital Transformation, society is facing a global problem – cybercrime. Every single day, the management of different companies experiences more difficulties in ensuring prevention from hacker attacks. Prevention from cyberattacks is becoming an international problem for businesses, causing significant financial losses. For the aim of the article, some sectors were analyzed – the insurance and banking industry which face the challenge of “cybercrime” because their activities are almost completely digitalized. It is important to notice the arguments of the competent authorities investigating cybercrime. The whole digitalization of the business processes in enterprises requires additional resources for combating this kind of crime. The anonymous nature of these acts also threatens international security. Operational authorities also face these challenges. A change in international law regulation is necessary, in the management directed against digital risks and anomalies in IT security in administration and business.